Structural development and energy dissipation in simulated silicon apices - Jarvis, Samuel Paul; Kantorovich, Lev; Moriarty, Philip (Beilstein Journal of Nanotechnology, 2013)
In this paper we examine the stability of silicon tip apices by using density functional theory (DFT) calculations. We find that some tip structures - modelled as small, simple clusters - show variations in stability during manipulation dependent on their orientation with respect to the sample surface. Moreover, we observe that unstable structures can be revealed by a characteristic hysteretic behaviour present in the F(z) curves that were calculated with DFT, which corresponds to a tip-induced dissipation of hundreds of millielectronvolts resulting from reversible structural deformations. Additionally, in order to model the structural evolution of the tip apex within a low temperature NC-AFM experiment, we simulated a repeated tip–surface indentation until the tip structure converged to a stable termination and the characteristic hysteretic behaviour was no longer observed. Our calculations suggest that varying just a single rotational degree of freedom can have as measurable an impact on the tip–surface interaction as a completely different tip structure.
Keywords: apex structure; atomic force microscopy; DFT; dissipation; hysteresis; NC-AFM; silicon; spectroscopy; tip structure